Nutritional composition and angiotensin converting enzyme inhibitory activity of blue lupin (Lupinus angustifolius) - Chin, Ying Yee; Chew, Lye Yee; Toh, Gaik Theng; Salampess, Junus; Azlan, Azrina; Ismail, Amin (Elsevier, 2019)
AMIN BIN ISMAIL/ Chew Lye Yee// CHIN YING YEE,AZRINA BINTI AZLAN/// Gaik Theng Toh,Junus Salam Pessy